BAGHAYUN BALAM REPRESENTASI DARI LAGU ANAK BALAM DI NAGARI KOTO TARATAK PESISIR SELATAN - Sinta Ovela; Yunaidi Yunaidi; Arnailis Arnailis (Jurnal Musik Nusantara, 2023)
The composition "Baghayun Balam" is a composition that departs from the tradition of the traditional song "anak balam" which is found in Nagari Koto Taratak, Sutera District, Pesisir Selatan Regency. In the beginning, this song was used in the ritual treatment of sick people, due to the influence of jinn and demons brought by other people such as witchcraft. Today the song "anak balam" has entered the realm of the rabab pasisia performing arts accompanied by the rabab pasisia and gandang oyak instruments. the song "anak balam" is usually sung in pairs (male and female) with verses that tell about the existence of subtle people in a continuous way that has a real sequence game technique, namely focusing on repetition or repetition by moving the basic tone from low to high and then back to reshape. The song "anak balam" became an inspiration for the artist to serve as material in creating a new piece of musical composition entitled "Baghayun Balam" which was worked on using a Tradition approach by Waridi who stated that the Traditional Approach is a process of creation that uses traditional idioms. which originates from Javanese karawitan without losing its original tradition. This work consists of three parts, namely the beginning, the middle, and the end which are intended to contribute to the development of traditional art so that its sustainability is maintained so that it can adapt and develop according to the mindset of the supporting community